The path of ambivalence: tracing the pull of opposing evaluations using mouse trajectories - Schneider, Iris K.; van Harreveld, Frenk; Rotteveel, Mark; Topolinski, Sascha; van der Pligt, Joop; Schwarz, Norbert; Koole, Sander L. (Frontiers in Psychology, 2015)
Ambivalence refers to a psychological conflict between opposing evaluations, often experienced as being torn between alternatives. This dynamic aspect of ambivalence is hard to capture with outcome-focused measures, such as response times or self-report. To gain more insight into ambivalence as it unfolds, the current work uses an embodied measure of pull, drawing on research in dynamic systems. In three studies, using different materials, we tracked people’s mouse movements as they chose between negative and positive evaluations of attitude objects. When participants evaluated ambivalent attitude objects, their mouse trajectories showed more pull of the non-chosen evaluative option than when they evaluated univalent attitude objects, revealing that participants were literally torn between the two opposing evaluations. We address the relationship of this dynamic measure to response time and self-reports of ambivalence and discuss implications and avenues for future research.